The NO/cGMP pathway inhibits Rap1 activation in human platelets via cGMP-dependent protein kinase I - Danielewski, Oliver; Schultess, Jan; Smolenski, Albert (Thrombosis and Haemostasis, 2005)
The NO/cGMP signalling pathway strongly inhibits agonist-induced platelet aggregation. However, the molecular mechanisms involved are not completely defined. We have studied NO/cGMP effects on the activity of Rap1, an abundant guanine-nucleotidebinding protein in platelets. Rap1-GTP levels were reduced by NO-donors and activators of NO-sensitive soluble guanylyl cyclase. Four lines of evidence suggest that NO/cGMP effects are mediated by cGMP-dependent protein kinase (cGKI): (i) Rap1 inhibition correlated with cGKI activity as measured by the phosphorylation state ofVASP, an established substrate of cGKI, (ii) 8-pCPT-cGMP, a membrane permeable cGMP-analog and activator of cGKI, completely blocked Rap1 activation, (iii) Rp- 8pCPT-cGMPS, a cGKI inhibitor, reversed NO effects and (iv) expression of cGKI in cGKI-deficient megakaryocytes inhibited Rap1 activation. NO/cGMP/cGKI effects were independent of the type of stimulus used for Rap1 activation. Thrombin-,ADPand collagen-induced formation of Rap1-GTP in platelets as well as turbulence-induced Rap1 activation in megakaryocytes were inhibited. Furthermore, cGKI inhibited ADP-induced Rap1 activation induced by the G α i -coupled P2Y12 receptor alone, i.e. independently of effects on Ca2+-signalling. From these studies we conclude that NO/cGMP inhibit Rap1 activation in human platelets and that this effect is mediated by cGKI. Since Rap1 controls the function of integrin α IIbβ 3 , we propose that Rap1 inhibition might play a central role in the anti-aggregatory actions of NO/cGMP.
Keywords: cGMP; kinase; nitric oxide; platelet physiology; Rap1